2015
DOI: 10.3389/fmicb.2015.00780
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol mechanism by root-associated Bacillus amyloliquefaciens FZB42 – a review

Abstract: Bacillus amyloliquefaciens subsp. plantarum FZB42 is a Gram-positive model bacterium for unraveling plant–microbe interactions in Bacilli. In addition, FZB42 is used commercially as biofertilizer and biocontrol agent in agriculture. Genome analysis of FZB42 revealed that nearly 10% of the FZB42 genome is devoted to synthesizing antimicrobial metabolites and their corresponding immunity genes. However, recent investigations in planta demonstrated that – except surfactin – the amount of such compounds found in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
354
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(379 citation statements)
references
References 66 publications
(94 reference statements)
10
354
1
14
Order By: Relevance
“…Bacillus spp. are widely used commercially as biofertilizer and biocontrol agents in agriculture due to their spore forming ability and stability in [71]. It is interesting to note that in our taxonomic profiling, Bacilli abundance was extremely low in the four compartments analyzed, with a maximum abundance of 0.016 % of the total reads.…”
Section: Isolation Of Putative Endophytic Bacteria Determination Of mentioning
confidence: 83%
“…Bacillus spp. are widely used commercially as biofertilizer and biocontrol agents in agriculture due to their spore forming ability and stability in [71]. It is interesting to note that in our taxonomic profiling, Bacilli abundance was extremely low in the four compartments analyzed, with a maximum abundance of 0.016 % of the total reads.…”
Section: Isolation Of Putative Endophytic Bacteria Determination Of mentioning
confidence: 83%
“…produce a wide range of biological active compounds that suppress development of many plant pathogens (Zhao et al 2012). However, a recent investigation demonstrated that the amount of antifungal or antibacterial compounds released by this bacteria in the rhizosphere is relatively low, raising doubts that a direct suppression of plant pathogens plays a major role (Chowdhury et al 2015). More likely, it seems that the main mechanism responsible for biocontrol activity is the induced systemic resistance (ISR) triggered by compounds produced by Bacillus spp.…”
Section: Mcloughlin Et Al 1992mentioning
confidence: 99%
“…Lipopeptides (LPs) structurally consist of a cyclic peptide joined to a chain of β-hydroxy or β-amino fatty acids ( Figure 4-A), classified into 3 different families (iturines, fengicines and surfactines), according to their amino acid sequences and length of the fatty acid (Ongena and Jaques, 2008;Falardeau et al, 2013). These molecules are synthesized by multienzymatic complexes, known as nonribosomal peptide synthetase (NRPS), which are independent to messenger RNA (Chowdhury et al, 2015). The families of iturines, fengicines and surfactines have been widely studied for their antibacterial and antifungal activity (Meena and Kanwar, 2015).…”
Section: Production Of Lipopeptidesmentioning
confidence: 99%
“…This has led to the study of multiple mechanisms used by the BCA to control the growth, development and infection of phytopathogenic organisms in diverse economically important crops; some of the most important of these mechanisms include: a) contact mechanisms such as hyperparasitism and predation (Chen et al, 2016); b) the production of compounds with low molecular weights with a direct effect on the growth of the antibiotic pathogen (phenazines, 2,4-diacetylfluoroglucinol, cyclic lipopeptides), lytic enzymes (chitnases, glucanases, proteases), products of unregulated residues (ammonia, carbon dioxide, hydroxide cyanide) (Yan et al, 2011;Zhang et al, 2016;Jaaffar et al, 2017;Piechulla et al, 2017) and c) indirect mechanisms from the competition for space and nutrients (consumption of leached-exudates, production of siderophores, induction to the systemic response in plants through the production of phytohormones and molecular patterns) (Pal and Gardener, 2006;Yu et al, 2011;Chowdhury et al, 2015). These action mechanisms have been observed in the microbial strains used as BCA, in which the Bacillus genus has been widely studied due to its high abundance and diversity in agro-systems (soil, water and plant), with a significantly higher population in comparison to other microbial genera, and also due to its diverse metabolic capabilities, with an outstanding capability to produce antibiotics and other antimicrobial and antifungal metabolites bajo peso molecular con efecto directo sobre el crecimiento del patógeno antibióticos (fenazinas, 2,4-diacetilfloroglucinol, lipopéptidos cíclicos), enzimas líticas (quitinasas, glucanasas, proteasas), productos de residuos no regulados (amoniaco, dióxido de carbono, cianuro de hidróxido) (Yan et al, 2011;Zhang et al, 2016;Jaaffar et al, 2017;Piechulla et al, 2017) y c) mecanismos indirectos por competencia de espacio y nutrientes (consumo de lixiviados-exudados, producción de sideróforos, inducción a la respuesta sistémica en plantas mediante la producción de fitohormonas y patrones moleculares) (Pal y Gardener, 2006;Yu et al, 2011;Chowdhury et al, 2015). Estos mecanismos de acción han sido observados en las cepas microbianas utilizadas como ACB, entre las cuales el género Bacillus ha sido ampliamente estudiado debido a su alta abundancia y diversidad en los agro-sistemas (suelo, agua y planta), siendo significativamente mayor su población en comparación a otros géne-ros microbianos, y además por sus diversas capacidades metabólicas, destacando su capacidad para producir antibióticos y otros metabolitos antimicrobianos y antifúngicos (Tejera-Hernández et al, 2011).…”
Section: Introductionmentioning
confidence: 99%